Development of non‐destructive analytical strategies based on Raman spectroscopy and complementary techniques for Mars Sample Return tested on Northwest Africa 1950 Martian meteorite. (14th September 2022) - Coloma, Leire; García‐Florentino, Cristina; Huidobro, Jennifer; Torre‐Fdez, Imanol; Aramendia, Julene; Arana, Gorka; Castro, Kepa; Madariaga, Juan Manuel
Abstract: The Mars Sample Return (MSR) is a near future mission to return samples from the surface of Mars to the Earth. The field operations to carry out data collection, selection of the samples, and sampling procedure, mainly related to the CanMars MSR analog mission, are well‐studied and published. In contrast, studies related to the methodology implemented to characterize the mineralogy of the returned samples are scarcer and focused on biosignature detection. This work presents a non‐destructive analytical methodology based on Raman microscopy (single point and imaging), micro‐energy dispersive X‐ray fluorescence imaging analysis, and scanning electron microscopy coupled to energy dispersive spectroscopy that could be used as a first analytical characterization for the Martian samples that will be returned to the Earth in the upcoming MSR mission, before any destructive analysis. The analytical methodology has been tested on a fragment of the Northwest Africa 1950 Martian meteorite, which gives us a mineralogical characterization of the meteorite. This methodology also allowed to define several chemical reactions taking place in some of the mineral phases (olivines and ilmenite) of the meteorite. In addition to the geochemical characterization of the samples, the fact that this methodology allows to assess the chemical transformations in several minerals gives important clues for describing mineral processes and geological evolution that took place on Mars. This work also shows the advantages and disadvantages that each of the techniques employed has when performing a mineralogical characterization, the information that each one can provide and the importance of combining them. Abstract : A non‐destructive analytical methodology, based on Raman microscopy (single point and imaging), micro‐energy dispersive X‐ray fluorescence (μED‐XRF) imaging analysis, and scanning electron microscopy coupled to energy dispersive spectroscopy (SEM‐EDS), is suggested for a first analytical characterization for the Martian samples that will be taken to the Earth in the upcoming MSR mission. The methodology has been tested on a sample of the Martian NWA1950 meteorite.